Incidence of skeletal-related events in patients with breast or prostate cancer-induced bone metastasis or multiple myeloma: A 12-year longitudinal nationwide healthcare database study. (August 2019) - Baek, Yeon-Hee; Jeon, Ha-Lim; Oh, In-Sun; Yang, Hyowon; Park, Jeehye; Shin, Ju-Young
Highlights: South Korean cohort included 53, 231 patients with bone metastasis or multiple myeloma. SRE incidences in South Korea were slightly higher than those in Europe. The cumulative SRE incidence was 47%, 31.4%, and 38.0% in BC, PC, and MM patients. Abstract: Background: This study examined the incidence of skeletal-related events (SRE) among patients with breast cancer (BC)- or prostate cancer (PC)-induced bone metastasis or multiple myeloma (MM) based on a population-based, 12-year healthcare database. Methods: Patients aged ≥18 years with bone metastasis from BC or PC or with MM between 2004 and 2015 were included. SRE was defined as pathologic fracture, spinal cord compression, radiation, or surgery to bone. Patients were followed-up from the initial diagnosis of bone metastasis (for those with BC or PC) or MM until SRE occurrence. To estimate multiple SREs, we applied a 21-day time window to ensure that subsequent SREs occurred independently from the previous event. We calculated the incidence and 95% confidence intervals (CIs), stratified according to the previous SRE history. Results: Our cohort included 53, 231 patients, including 23, 811 with BC, 19, 170 with PC, and 10, 250 with MM. The incidence of multiple SREs in the 21-day time window was 1.03 (95% CI = 1.01–1.05) in patients with previous SRE history and 0.19 (95% CI = 0.19–0.20) in those without. The cumulative SRE incidences were 47%, 31.4%, and 38.0% in BC, PC, and MM patients. Conclusion: The incidences of multiple SREs in BC- or PC-induced bone metastasis or MM in this 12-year South Korean cohort were slightly higher than those in European countries. Our study provided real-world evidence that patients with BC- or PC-induced bone metastasis or MM are at high risk of SRE.